AFIKSASI DALAM¬ BAHASA TOLAKI - Wawan, Wawan (Aksara Public, 2019)
This research entitled "Affixation in Tolaki Language" is a research on Tolaki language in Konawe district, Southeast Sulawesi, which examines phonemes, morphemes, words, phrases, clauses, sentences, and discourses. In this study will use the morpheme language unit for study. The formulation of the problem in this study are: 1) What are the functions and meanings of Affix? 2) What is the process of affixation in the Tolaki language? The purpose of this study is: To describe the affixation process in Tolaki language and to know the function and meaning of affixation. Morfem bound in Tolaki language there are several types, including (i) Prefixes are prefixes that are located at the beginning of the basic form in this study there are prefixes including: me, ma, ine, no. (ii) Infix is ​​an insert that is located in the middle of the basic form in this study, there is an infix: i, no (iii) Suffix is ​​a suffix located at the end of the basic form in this study, there are suffixes: no, i, ikaa, to, and ( iv) Confix is ​​a combination of affixes on the basic form, in this study there are confixes including: me- ... i, pe -...- no, no -...- i, no -... to. And the word formation process in the Tolaki language is in the prefix, infix, suffix and confix.